Symmetric and asymmetric nexus between economic policy uncertainty, oil price, and renewable energy consumption in the United States, China, India, Japan, and South Korea: Does technological innovation influence? - Rong, Guo; Qamruzzaman, Md (Frontiers in Energy Research, 2022)
The motivation of the study is to gauge the impact of economic policy uncertainty, oil price and technological innovation on renewable energy consumption in the Top 5 oil-importing nations for the period. The study employed a linear and nonlinear framework in exploring the association and variable elasticities on renewable energy consumption. According to linear assessment, the study documented positive effects from technological innovation and oil price volatility, whereas economic policy uncertainty adversely caused renewable energy integration, especially in the long run. The study disclosed long-run and short-run asymmetric connections between TI, EPU, and REC for asymmetric assessment. For the case of directional causality, the study documented feedback hypothesis holds in to explain the nexus between oil price and renewable energy consumption in China [OILREC], economic policy uncertainty and renewable energy consumption [EPUREC] in china, India, Japan and south-Korea, and technological innovation and renewable energy consumption [TIREC] in south-Korea. On a policy note, the study established that efficient energy transition from fossil fuel to renewable energy demands economic stability and, therefore, stability must be ensured. Furthermore, oil prices should be considered while formulating energy policies